2017
DOI: 10.1111/ajad.12607
|View full text |Cite
|
Sign up to set email alerts
|

Increased habenular connectivity in opioid users is associated with an α5 subunit nicotinic receptor genetic variant

Abstract: Background and Objectives Opioid use disorder (OUD) is a chronic disorder with relapse based on both desire for reinforcement (craving) and avoidance of withdrawal. The aversive aspect of dependence and relapse has been associated with a small brain structure called the habenula, which expresses large numbers of both opioid and nicotinic receptors. Additionally, opioid withdrawal symptoms can be induced in opioid-treated rodents by blocking not only opioid, but also nicotinic receptors. This receptor co-locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
6
15
0
Order By: Relevance
“…Psychiatric inpatients ( N = 423) were recruited from the Menninger Clinic in Houston, Texas as a part of the McNair Initiative for Neuroscience Discovery—Menninger/Baylor (MIND‐MB) research study . Inpatients were eligible if mentally stable enough to participate, had no contraindications for magnetic resonance imaging (MRI), and gave signed, informed consent (procedures were approved by the Institutional Review Board).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric inpatients ( N = 423) were recruited from the Menninger Clinic in Houston, Texas as a part of the McNair Initiative for Neuroscience Discovery—Menninger/Baylor (MIND‐MB) research study . Inpatients were eligible if mentally stable enough to participate, had no contraindications for magnetic resonance imaging (MRI), and gave signed, informed consent (procedures were approved by the Institutional Review Board).…”
Section: Methodsmentioning
confidence: 99%
“…The habenular circuit has been implicated in depression . We created the habenula left and right ROIs manually in SPM8 (one individually placed voxel per side) according to previous publications from our lab . The locus coeruleus, dorsal raphe, median raphe, substantia nigra, and ventral tegmental area (VTA) are all a part of habenular circuitry , and they have been implicated in depression and in some cases suicidal behavior specifically .…”
Section: Methodsmentioning
confidence: 99%
“…Anterior cingulate cortex and striatum were defined as in the Automated Anatomical Labeling (AAL) atlas (Tzourio-Mazoyer et al, 2002). The habenula was manually defined for each participant as two individual bilateral voxels using the T1 image as guide, as in (Curtis et al, 2017). Functional images were down-sampled to 3 9 3 9 3 to mitigate partial volume issues.…”
Section: Imagingmentioning
confidence: 99%
“…Furthermore, Peng et al (2018) found that structural connectivity of the lingual gyrus differentiated heavy smokers from light smokers and controls: Heavy smokers had significantly greater white matter atrophy of the lingual gyrus. Although no previous research has found aberrant habenula-lingual connectivity in smokers, habenula-lingual abnormalities in individuals with schizophrenia (Zhang et al, 2017) and high "negative connectivity" between the habenula and lingual gyrus in both healthy controls and psychiatric patients have been reported (Curtis et al, 2017;Ely et al, 2016).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 89%
“…As a part of the first-level analysis, we chose our seeds of interest, the right and left habenula. The seeds were manually created for each participant using the participant's structural T1 MRI as a guide (Curtis et al, 2017). Correlation maps were produced by extracting the BOLD time-course from the habenula seed, followed by generating Pearson's correlation coefficients between the seed time course and the time courses of all other voxels in the brain.…”
Section: Rsfc Analysesmentioning
confidence: 99%